2013
DOI: 10.1007/s11906-013-0332-9
|View full text |Cite
|
Sign up to set email alerts
|

A Consideration of Genetic Mechanisms Behind the Development of Hypertension in Blacks

Abstract: Hypertension is a more serious disease in blacks. The determinants of the blood pressure (BP) may be uniquely different from those in whites. The characteristic low-renin, salt-sensitive hypertension of blacks is consistent with the kidney reabsorbing additional sodium (Na), which leads to an expanded plasma volume that drives the BP. Mechanisms considered are genetically based. These include: (1) the intra-renal renin-angiotensin system (RAS), one based on molecular variations in angiotensinogen; (2) the Na, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…Numerous studies have outlined the possible genetic contributors to HTN among blacks [26][27][28][29][30]. Blacks exhibit low renin levels, leading to additional sodium reabsorption by the kidneys, which in turn contributes to elevated BP [26,27].…”
Section: Genetic Mechanisms In Hypertensionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have outlined the possible genetic contributors to HTN among blacks [26][27][28][29][30]. Blacks exhibit low renin levels, leading to additional sodium reabsorption by the kidneys, which in turn contributes to elevated BP [26,27].…”
Section: Genetic Mechanisms In Hypertensionmentioning
confidence: 99%
“…Blacks exhibit low renin levels, leading to additional sodium reabsorption by the kidneys, which in turn contributes to elevated BP [26,27]. Additionally, a more active sodium-potassiumchloride cotransporter in the thick ascending limb of the kidneys has been associated with multiple phenotypes in blacks [26,27].…”
Section: Genetic Mechanisms In Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tu and Pratt concluded that the low-renin, salt sensitivity of BP phenotype of AD compared with ED is attributed to alterations in genetic makeup (36). They went on to describe greater renal Na + absorption among AD compared with ED, thus leading to expanded plasma volume in this population.…”
Section: Discussionmentioning
confidence: 99%
“…In AAs, hypertension is generally considered related to high reabsorption of sodium (Na) and this low-renin, salt-sensitive hypertension may be, at least in part, genetically-based, with a more active Na, potassium (K), 2 chloride cotransporter (NKCC2), and its regulators in the thick ascending limb [25]. Although, urinary excretion of Na appears similar in Blacks and Whites, indicating similar dietary Na intakes, urinary excretion of K is generally lower in AAs [26].…”
Section: Unmasking Pathophysiology and Genetic Mechanisms For Hypertementioning
confidence: 99%